Estimating the Potential Blue Carbon Gains From Tidal Marsh Rehabilitation: A Case Study From South Eastern Australia - Gulliver, Anne; Carnell, Paul E.; Trevathan-Tackett, Stacey M.; Duarte de Paula Costa, Micheli; Masqué, Pere; Macreadie, Peter I. (Frontiers in Marine Science, 2020)
Historically, coastal ‘blue carbon’ ecosystems (tidal marshes, mangrove forests, seagrass meadows) have been impacted and degraded by human intervention, mainly in the form of land acquisition. With increasing recognition of the role of blue carbon ecosystems in climate mitigation, protecting and rehabilitating these ecosystems becomes increasingly more important. This study evaluated the potential carbon gains from rehabilitating a degraded coastal tidal marsh site in south-eastern Australia. Tidal exchange at the study site had been restricted by the construction of earthen barriers for the purpose of reclaiming land for commercial salt production. Analysis of sediment cores (elemental carbon and 210Pb dating) revealed that the site had stopped accumulating carbon since it had been converted to salt ponds 65 years earlier. In contrast, nearby remnant (‘control’) tidal marsh areas are still accumulating carbon at relatively high rates (0.541 tonnes C ha-1 yr-1). Using elevation and sea level rise data, we estimated the potential future distribution of tidal marsh vegetation if the earthen barrier were removed and tidal exchange was restored to the degraded site. We estimated that the sediment-based carbon gains over the next 50 years after restoring this small site (equivalent to ~124 football fields in area) would be 8,877 tonnes, which could offset the annual emissions of ~7,000 passenger cars (at 4.6 metric tonnes pa.) or ~1,400 Australians. Overall, we recommend that this site is a promising prospect for rehabilitation based on the opportunity for blue carbon additionality, and that the business case for rehabilitation could be bolstered through valuation of other co-benefits, such as nitrogen removal, support to fisheries, sediment stabilization, and enhanced biodiversity.